(3fXGe GdZQjHs - (3YjSi Hf EHQGgje GdQHYj, CHh eMeO,J (B480 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdCTjGA ef GdYOe Edi GdhLhO s
(3BNQgG (B:s
(3EPG LGA Vja LGA ddVja Vjajf aChOG eG JbQG GdVjha GdVjGajf Je cJGH fXGe GdJZQjH s
(3GdfSNI HgG MhGTs
(3ai ChdgG bQGAI ddCejQ YKeGf Hf GdCejQ TLGY GdOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B100s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GddZIs